Números primos e o Postulado de Bertrand - Ferreira, Antônio Eudes (2014)
This work presents a study of prime numbers, how they are distributed, how many prime numbers are there between 1 and a real number x, formulas that generate primes, and a generalization to Bertrand's Postulate. Six proofs that there are in nitely many primes using reductio ad absurdum, Fermat numbers, Mersenne numbers, Elementary Calculus and Topology are discussed.